Friday
May 6, 2016

Posts by Evelina

Total # Posts: 17

math
How many solutions equation x^4 + 2x^2 - 15 = 0 has?
April 28, 2012

math
Helped alot! Thank you!
April 28, 2012

math
April 28, 2012

biology
I have codone AUG. Which one of amino acids will be involved in protein making, if nucleotide with adenine (A) will be changed to nucleotide with cytosine (C)?
February 8, 2012

science
V(CH3OH)= 2 litres ρ(CH3OH) = 0,80 g/ml v(O2) - ? (How much O2 is it needed to burn with 2 litres of CH3OH?)
January 30, 2012

chemistry
V(CH3OH)= 2 litres ρ(CH3OH) = 0,80 g/ml v(O2) - ? (How much O2 is it needed to burn with 2 litres of CH3OH?)
January 30, 2012

trig
If (cosa-sina)/sina = 2 , then what is tga = ?
December 9, 2011

trig
ehh, still dont get it.
December 7, 2011

trig
I need to prove parallelogram law using the law of cosines. 2AB^2 + 2BC^2 = AC^2 + BD^2 Please, help me to do this.
December 7, 2011

trig
How to prove the theorem of sines, using S=(a*b/2) * sin γ ?
December 2, 2011

trig
I need to count this: a) 1-tg^2a/1+ctg^2a, when sina =2/3 b) 1-tg^2a/1-ctg^2a, when cosa= -1/3 c) tga * cos^2a, when sina + cosa=5/7 d) tg^2a + 1/sina * 1/cosa + ctg^2a, when tga + ctga =5
November 30, 2011

trig
Well, that‘s what the question says. I can send a picture of it, if you don‘t believe. Show me how you do it with brackets, maybe I‘ll know what to do with that one.
November 30, 2011

trig
The b) actually was like this in my book: sin^2x/sinx-cosx - sinx+cosx/tg^2x+1 = sinx + cosx
November 30, 2011

trig
I need to prove equality. a) (sina + cosa)^2 -1 / ctga - sinacosa = 2tg^2a b) (sin^2x/sinx-cosx) - (sinx+cosx/tg^2x+1) = sinx + cosx c) sin^4a - sin^2a - cos^4a + cos^2a = cosπ/2 How to do these?
November 30, 2011

trig
How to do this one? (sina/1-cosa) + (1-cosa/sina) = Also, wanted to ask if I did another one right: 1 - sin^2a + tg^2a * cos^2a = 1 - sin^2a + (sina/cosa)^2 * cos^2a = 1 - sin^2a + sin^2a = 1 ???
November 12, 2011

trig
oh yes, I wrote the first one wrong. THANK YOU
November 12, 2011

trig
Please help me how to do this: 1) 1 + sina*cosa / (cosa + sina)^2 = 2) sina + cosa / 1- 2sin^2a =
November 12, 2011

1. Pages:
2. 1